Similarity of bacterial populations in saliva from African-American mother-child dyads (2007)
Using PCR-based denaturing gradient gel electrophoresis analyses of oral bacterial samples in 20 mother-child dyads, this study demonstrated a high degree of similarity of bacterial compositions between the mothers and their children; the two may share as much as 94% of their oral bacterial spectra, including cariogenic species.